Recognition memory: Adding a response deadline eliminates recollection but spares familiarity - Sauvage, Magdalena M. (Cold Spring Harbor Laboratory Press, 2010)
A current controversy in memory research concerns whether recognition is supported by distinct processes of familiarity and recollection, or instead by a single process wherein familiarity and recollection reflect weak and strong memories, respectively. Recent studies using receiver operating characteristic (ROC) analyses in an animal model have shown that manipulations of the memory demands can eliminate the contribution of familiarity while sparing recollection. Here it is shown that a different manipulation, specifically the addition of a response deadline in recognition testing, results in the opposite performance pattern, eliminating the contribution of recollection while sparing that of familiarity. This dissociation, combined with the earlier findings, demonstrates that familiarity and recollection are differentially sensitive to specific memory demands, strongly supporting the dual process view.